PTU-304 Cost-effectiveness of current therapies in primary biliary cirrhosis: a systematic review of economic evidence. (22nd June 2015) - Pells, G; Jones, D; Vale, L
Abstract : Introduction: Primary Biliary Cirrhosis (PBC) is an autoimmune chronic cholestatic liver disease. One therapy, ursodeoxycholic acid (UDCA), is FDA approved. Many patients, however, do not respond to this treatment. Serious medical morbidity, impact on patient quality of life (QoL), and mortality are not uncommon despite UDCA therapy. This study set out to assess the economic evidence for current PBC therapies in order to inform the development and implementation of novel therapies. Method: A systematic review of cost and cost-effectiveness evidence for recognised therapies in PBC was conducted. Data were extracted from relevant studies and assessed for quality in accordance with Centre for Reviews and Dissemination guidelines. Results: Only two studies, both of UDCA cost-effectiveness, were identified. Although deriving data from randomised controlled trials, no justification for selection of positive UDCA effectiveness data in a broad and ambiguous field was given. A maximum of 5 years of UDCA therapy was studied. Estimates of cost ranged from US1372 saving per year of therapy, to an extrapolated disease lifetime saving of EUR 6338 per treated patient. Both studies assessed cost from a direct hospital-based perspective only, with no inclusion of primary care costs or adjustment for QoL. Conclusion: This work is the first systematic review of economic evaluations in PBC. No current or comprehensive economic evaluations of PBC treatments exist. A PBC model informed by recent advances in disease understanding is required to facilitate estimation of the economic burden of PBC and evaluation of cost-effectiveness of novel therapies currently undergoing clinical trials. Disclosure of interest: None Declared.